Implications of helplessness in depression: diagnosing mild cognitive impairment and analyzing its effects on cognitive decline in older adults - Lee, Boung Chul; Choe, Young Min; Suh, Guk-Hee; Keum, Musung; Kim, Shin Gyeom; Kim, Hyun Soo; Hwang, Jaeuk; Yi, Dahyun; Kim, Jee Wook (Frontiers in Aging Neuroscience, 2024)
Background: This study focuses on how elements of depression correlate with mild cognitive impairment (MCI) in older adults and the diagnostic efficacy of combining these components with the Mini-Mental State Examination (MMSE). The study also investigated the connection between individual depression components and overall cognitive function, as measured by the total score (TS) of the consortium to establish a registry for Alzheimer’s disease (AD) assessment battery. Methods: The study included 196 nondemented adults aged 65 to 90 years at a university hospital and community. Comprehensive clinical assessments including the 30-item Geriatric Depression Scale (GDS) to measure components of depressive symptoms, TS, and blood nutritional biomarkers. Results: Our stepwise logistic regression analysis highlighted the 'helplessness item' (odds ratio = 4.531, 95% CI = 2.218 to 9.258, p < 0.001) as a significant predictor for MCI diagnosis. Further, models incorporating 'helplessness item + MMSE' demonstrated markedly enhanced accuracy in diagnosing MCI, surpassing the performance of the MMSE used independently. Notably, the group characterized by helplessness showed a significant reduction in TS (B = -5.300, SE = 1.899, β = -0.162, p = 0.006), with this trend being particularly pronounced in individuals exhibiting lower levels of physical activity. Interestingly, this correlation did not manifest in participants with higher physical activity levels. Conclusions: Our findings suggest that helplessness is highly effective in diagnosing MCI and is linked to a decrease in cognitive function. Therefore, when addressing MCI and AD-related cognitive decline, clinicians should consider helplessness.